A new quaternary Li0.19Al2.72O3.64N0.36 transparent ceramic with high hardness. (1st July 2021) - Chen, Qiangguo; Wang, Hao; Zheng, Kaiping; Xu, Pengyu; Ren, Lu; Tu, Bingtian; Wang, Weiming; Fu, Zhengyi
Abstract: A new quaternary Li0.19 Al2.72 O3.64 N0.36 transparent ceramic with the Vickers hardness of 17.91 ± 0.2 GPa at a load of 9.8 N and the in-line transmittance of 83.4% at 3.5 µm was prepared by hot isostatic press sintering (HIP) after pressureless sintering. The 7 Li and 27 Al magic-angle spinning (MAS) NMR spectra combined with the XRD Rietveld refinement was adopted to analyze the crystal structure. It is revealed that all the lithium ions are located in octahedra and the cation vacancies are mainly concentrated in tetrahedra. Based on the bond valance models, the complicated relationship among composition, crystal structure and intrinsic hardness of the spinel-type transparent ceramic were disclosed. Compared with the γ-AlON, the higher hardness of Li0.19 Al2.72 O3.64 N0.36 transparent ceramic is attributed to the coupling effect of enhanced hardness of bonds in octahedra and the slightly weakened hardness of bonds in tetrahedra. Graphical abstract: Image, graphical abstract